Being Foreigner in Their Own Land: The Samin Movement in Madiun East Java in Early Twentieth-Century - Wahyudhi, Johan (Universitas Hamzanwadi, 2024)
This article explains that the movement of the Samin community at the end of the 19th century in Java caused a stir in colonial society. Typical of village communities in general, they spent their days in agrarian activities. However, there was a problem, which caused them to migrate to several areas in East Java, including Madiun, and then they were known to have carried out a number of acts of resistance against the local colonial government. This research will use historical research methods, armed with reading a number of documents and archives left by the Dutch East Indies Government. The concept of social movement becomes the locus that is put forward to explore the various activities of the Orang Samin in their new areas. The purpose of writing this article is to show that the end of the 19th century became a period of crisis for Madiun, where various elements of popular resistance emerged to oppose the arrogance of the Dutch East Indies government.